High-Performance Ferroelectric Capacitors Based on Pt/BaTiO3/SrRuO3/SrTiO3 Heterostructures for Nonvolatile Memory Applications - Zengyuan Fang; Yiming Peng; Haiou Li; Xingpeng Liu; Jianghui Zhai (Crystals)
BaTiO3 (BTO), a lead-free chalcogenide ferroelectric material, has emerged as a promising candidate for ferroelectric memories due to its advantageous ferroelectric properties, notable flexibility, and mechanical stability, along with a high dielectric constant and minimal leakage. These attributes lay a crucial foundation for multi-value storage. In this study, high-quality BaTiO3 ferroelectric thin films have been successfully prepared on STO substrates by pulsed laser deposition (PLD), and Pt/BaTiO3/SrRuO3/SrTiO3 ferroelectric heterojunctions were finally prepared by a combination of UV lithography and magnetron sputtering. Characterization and performance tests were carried out by AFM, XRD, and a semiconductor analyzer. The results demonstrate that the ferroelectric heterojunction prepared in this study exhibits excellent ferroelectric properties. Furthermore, the device demonstrates fatigue-free operation after 107 bipolar switching cycle tests, and the polarization value exhibits no significant decrease in the holding characteristic test at 104 s, thereby further substantiating its exceptional reliability and durability. These findings underscore the considerable promise of BTO ferroelectric memories for nonvolatile storage applications and lay the foundation for the development in the fields of both in-memory computing systems and neuromorphic computing.